Invasive pulmonary aspergillosis in immunocompetent patients hospitalised with influenza A-related pneumonia: a multicenter retrospective study - Chen, Liang (BMC Pulm Med, 2020)
BACKGROUND: Increasing cases of pulmonary aspergillosis (IPA) in immunocompetent patients with severe influenza have been reported. Howevere, the risk factors for occurence and death are largely unknown. METHODS: Data of hospitalised patients with influenza A-related pneumonia (FluA-p) obtained from five teaching hospitals from 2031 to 2018, were reviewed. Univariate and multivariate logistical regression analyses were performed to determine the risk factors involved in the acquisition and 60-day mortality in IPA patients. RESULTS: Of the 693 FluA-p patients included in the study, 3.0% (21/693) were IPA patients with a 60-day mortality of 42.9% (9/21). Adjusted for confounders, a Cox proportional hazard model showed that IPA was associated with increased risk for 60-day mortality [hazard ratio (HR) 4.336, 95% confidence interval (CI) 1.191–15.784, p = 0.026] in FluA-p patients. A multivariate logistic regression model confirmed that age (odd ratio (OR) 1.147, 95% CI 1.048–1.225, p = 0.003), systemic corticosteroids use before IPA diagnosis (OR 33.773, 95% CI 5.681–76.764, p <  0.001), leukocytes > 10 × 10(9)/L (OR 1.988, 95% CI 1.028–6.454, p = 0.029) and lymphocytes < 0.8 × 10(9)/L on admission (OR 34.813, 95% CI 1.676–73.006, p = 0.022), were related with the acquisition of IPA. Early neuraminidase inhibitor use (OR 0.290, 95% CI 0.002–0.584, p = 0.021) was associated with a decreased risk for a 60-day mortality in IPA patients. CONCLUSIONS: Our results showed that IPA worsen the clinical outcomes of FluA-p patients. The risk factors for the acquisition and death were helpful for the clinicians in preventing and treating IPA.